VoI analysis of temporally continuous SHM information in the context of adaptive risk-based inspection planning. (November 2022) - Zhang, Wei-Heng; Qin, Jianjun; Lu, Da-Gang; Liu, Min; Faber, Michael Havbro
Abstract: Decision-making on integrity management strategy of engineering structures can be regarded as a time dependent problem, where optimal decisions change over the course of the operational service life depending on the information collecting in the past. Moreover, continuously collected SHM information is also closely related to time, in which the incompleteness of information and temporal effect on the reduction of epistemic uncertainties affecting the life-cycle costs are strongly affected by the timing of decisions. To consider the effects of incompleteness on the optimal decision making and the corresponding value of information (VoI), the present contribution focuses on the analysis of time-dependent and incomplete Structural Health Monitoring (SHM) information value within a framework of adaptive risk-based inspection (RBI) planning. To this end, results of past inspections and maintenance actions together with temporal continuous SHM information are jointly considered in the proposed framework. To account for the time-dependency and incomplete properties of SHM information, a thorough information modelling method is given, along with a simplified approach to the quantification of the VoI. The analysis approach is demonstrated through an example considering integrity management of a structural detail subject to fatigue degradation. The example results demonstrate the potential benefits of adaptive RBI planning and the value of fatigue stress information in the context of structural integrity management. Finally, the present work concludes with a discussion of limitations associated with the proposed schemes and points at the prospects for further investigations. Highlights: Adaptive thoughts associated with RBI planning and VoI analysis are presented. A probabilistic model of SHM information during the operation phase is presented. The potential benefit of adaptive RBI planning is investigated. Value of SHM information in adaptive RBI planning is analysed.